MENINGKATKAN KEMANDIRIAN PANGAN SELAMA PANDEMI COVID-19 DENGAN BUDIKDAMBER (BUDIDAYA IKAN DALAM EMBER) DI DESA MEKARWANGI - Fajra Wahyu Ramadhan; Suprihatin Suprihatin; Musyaffa Amin As-shabah (LPPM Universitas Islam 45, 2022)
Cultivation is one of the important sectors in human development and related to the environment in society. Cultivation that is easily carried out by the community with easy facilities and maintenance that does not require large capital is fish farming in buckets or often called BUDIKDAMBER. The method used in this research is to educate the public about fish farming in buckets. The result of cultivating fish in buckets is that people can cultivate in buckets which require small capital so it's easy to do.